DUPHASTON APPLICATION IN OBESE WOMEN WITH UTERINE MYOMA INFLUENCE ASSESSMENT ON LIPID METABOLISM - Guz, I.A.; Parashuk, Y.S. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
The research  was carried out to evaluate  the condition of  lipid metabolism in women with a fibromyoma of the uterus and obesity. The obtained data made it possible to us  ”Duphaston” drug in order to normalize the genital condition of women at the preoperative period.